Group versus Individual Liability : A Field Experiment in the Philippines - Giné, Xavier; Karlan, Dean S. (World Bank, Washington, DC, 2012)
Group liability is often portrayed as the key innovation that led to the explosion of the microcredit movement, which started with the Grameen Bank in the 1970s and continues on today with hundreds of institutions around the world. Group lending claims to improve repayment rates and lower transaction costs when lending to the poor by providing incentives for peers to screen, monitor, and enforce each other's loans. However, some argue that group liability creates excessive pressure and discourages good clients from borrowing, jeopardizing both growth and sustainability. Therefore, it remains unclear whether group liability improves the lender s overall profitability and the poor's access to financial markets. The authors worked with a bank in the Philippines to conduct a field experiment to examine these issues. They randomly assigned half of the 169 pre-existing group liability 'centers' of approximately twenty women to individual-liability centers (treatment) and kept the other half as-is with group liability (control). We find that the conversion to individual liability does not affect the repayment rate, and leads to higher growth in center size by attracting new clients.